Correction: Cheng, T.-M.; Hou, H.-Y. Intelligent Educational Evaluation of Research Performance between Digital Library and Open Government Data. Appl. Sci. 2022, 12, 791 - Tao-Ming Cheng; Hsing-Yu Hou (Applied Sciences, 2022)
In the published study, there was an error regarding the affiliation for Hsing-Yu Hou [...]